Thistle Control in Pastures - Brent Sellers; Pratap Devkota; Jason Ferrell (EDIS, 2019)
If left uncontrolled, thick thistle stands can reduce grazing, result in less forage production, and ultimately, lower calf weaning weight. A single thistle plant can produce at least 4,000 seeds, increasing the chance for higher thistle populations in the pasture the following year. Consequently, management practices need to be conducted prior to flower formation for effective thistle control. Even if thistles have not infested your pasture in the past, it is ideal that your pastures are scouted in late fall through mid-spring to ensure that thistles do not get out of control. New infestations are easier to manage than large-scale populations. This 3-page fact sheet is a minor revision written by Brent Sellers, Pratap Devkota, and Jason Ferrell, and published by the Agronomy Department, November 2019.